Analisis Pengaruh Rasio Likuiditas, Efisiensi Operasi, Kemampuan Pengelolaan Aktiva Produktif, Pinjaman Bermasalah dan Rasio Solvabilitas, Terhadap Kinerja Keuangan pada Bank Umum Swasta Nasional Periode 2017-2021 - Fidyani Anura Hidayati; Achmad Agus Priyono; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The study aims to determine. the Effect of Liquidity Ratio, Operating Efficiency, Ability to Manage Productive Assets, Non-Performing Loans and Solvency Ratio, on Financial Performance in National Private Commercial Banks for the 2017-2021 Period. .This research. uses a quantitative approach, by conducting empirical analysis, using panel data from 2017 to 2021. The sampling method used the purposive sampling method and 23 banks were selected as samples. The data analysis technique in this study is the regression analysis of panel data processed with SPSS. Based on the results of the panel data estimates, it shows that the variables of Liquidity Ratio (LDR), and Non-Performing Loans (NPL) have a significant effect on Financial Performance (ROA) at national private commercial banks in Indonesia in 2017-2021. Meanwhile, Operating Efficiency (BOPO), Productive Asset Management Ability (NIM), and Solvency Ratio (CAR) did not have a significant effect on Financial Performance (ROA) at National private commercial banks in Indonesia in 2017-2021. Keywords: Loan to Deposit Ratio (LDR), Operating Costs to Operating Income (BOPO), Net Interest Margin (NIM), Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Return On Assets (ROA)